Factors that Affect Coping Mechanisms in Chemotherapy Patients with the Approach of Callista Roy Adaptation Theory - Ifa Roifah; Elies Meilinawati; Tri Ratnaningsih; Rina Nur Hidayati (STIKes Patria Husada Blitar, 2019)
Chemotherapy could cause pain in the patient, thus causing the condition of the body would gradually weaken. This condition would make the patient delay the therapy due to physical symptoms and emotional pressure (psychological), which affected the seriousness of patients in the treatment and strong coping mechanism required to maintain good conditions One of the empirical evidence of conceptual model theory